Operation of a concentrated mode dual-alkali scrubber plant at the Lonmin smelter - Bezuidenhoudt, G.; Davis, J.; van Beek, B.; Eksteen, Jacques (The Southern African Institute of Mining and Metallurgy, 2012)
Lonmin Platinum installed a concentrated mode dual-alkali scrubber at the smelter in Marikana in 2002. The dual-alkali scrubber was the technology of choice at that time as a sulphur fixation plant, due to the perceived benefits of handling both the high SO2 concentrations of converter off-gas and the swings in SO2 concentration that are linked to Peirce-Smith operation. Owing to current and impending legislative requirements for air quality and waste, Lonmin is currently considering additions to the dual-alkali plant, but is also evaluating alternative technologies for sulphur fixation. This paper reviews the decision of Lonmin to install a concentrated mode dual-alkali scrubber and presents plant performance achieved. It also describes the important control variables and sensitivities of the plant, and the final product that is produced by the operation of the plant. The legislative requirement that drives the Lonmin technology evaluation is also discussed.